Thermal Degradation Behaviour of Ni(II) Complex of 3,4-Methylenedioxaphenylaminoglyoxime - Emin Karapınar; Ilkay Hilal Gubbuk; Bilge Taner; Pervin Deveci; Emine Ozcan (Journal of Chemistry)
Thermal degradation behaviour of the Ni(II) complex of 3,4-methylenedioxaphenylaminoglyoxime was investigated by TG, DTA, and DTG at a heating rate of 10°C min−1 under dinitrogen. The acquired experimental data shows that the complex is thermally stable up to 541 K. The pyrolytic decomposition process occurs by melting metal complex and metal oxide remains as final product. The energies of the reactions involved and the mechanism of decomposition at each stage have been examined. The values of kinetic parameters such as activation energy (E), preexponential factor (A) and thermodynamic parameters such as enthalpy (ΔH), entropy (ΔS), and Gibbs free energy (ΔG) are also evaluated.